What lies behind a fruit crop variety name? A case study of the barnī date palm from al‐'Ulā oasis, Saudi Arabia. Issue 1 (10th October 2022) - Gros‐Balthazard, Muriel; Battesti, Vincent; Flowers, Jonathan M.; Ferrand, Sylvie; Breil, Matthieu; Ivorra, Sarah; Terral, Jean‐Frédéric; Purugganan, Michael D.; Wing, Rod A.; Mohammed, Nahed; Bourgeois, Yann
Abstract : Societal Impact Statement: The oasis of al‐'Ulā is subject to a vast development operation by the central government of the Saudi monarchy. Agriculture is not strictly speaking the first objective of this initiative, the emphasis being on tourism and thus on the vast historical heritage and landscape qualities of the region. Nevertheless, agriculture and, in particular, phoeniculture remain the main resource for the inhabitants. Characterizing the local date palm agrobiodiversity is key to the sustainable development of oases. In al‐'Ulā, documenting indigenous knowledge about the locally predominant barnī variety and characterizing its genetic integrity and mode of propagation represents the essential leverage needed by farm development project planners to develop local production. Summary: Understanding how farmers name and categorize their crops in relation to the way they are propagated is critical for a proper assessment of agrobiodiversity. Yet, indigenous knowledge is often overlooked in genetic studies, which may result in an underestimation of crop diversity, thereby preventing its conservation and mobilization for developing sustainable agroecosystems. Here, we focus on the barnī date palm variety, a local elite variety of al‐'Ulā oasis, Saudi Arabia. We conducted an ethnobotanical survey on local phoeniculture practices and generated whole‐genome data to determine whether or not barnī palms are exclusively clonally (vegetatively) propagated. Further, we contrasted the genomes of barnī and two other palms from al‐'Ulā with 112 Phoenix spp. to provide an initial insight into date palm diversity in this oasis. The survey reveals that the dates of the barnī palm bear distinct names, depending on their quality. Results show that barnī is a true‐to‐type cultivar, indicating clonal propagation by offshoots with name maintenance, even between distinct cultivating situations in al‐'Ulā and a nearby oasis. Nonetheless, it is distinct from the prominent barnī cultivated in Oman. Its ancestry is comparable to other West Asian date palms, but another palm from this oasis shows influence from North Africa. What lies behind the cultivar name barnī in al‐'Ulā and further afield in the Arabian Peninsula has been deciphered through the key disciplinary combination of social anthropology and genetics. Future studies will provide additional insights into the original genetic make‐up of this millennia‐old oasis. Abstract : The oasis of al‐'Ulā is subject to a vast development operation by the central government of the Saudi monarchy. Agriculture is not strictly speaking the first objective of this initiative, the emphasis being on tourism and thus on the vast historical heritage and landscape qualities of the region. Nevertheless, agriculture and in particular phoeniculture remain the main resource for the inhabitants. Characterizing the local date palm agrobiodiversity is key to the sustainable development of oases. In al‐'Ulā, documenting indigenous knowledge about the locally predominant barnī variety and characterizing its genetic integrity and mode of propagation represents the essential leverage needed by farm development project planners to develop local production. Abstract : L'oasis d'al‐'Ulā fait l'objet d'une vaste opération de développement par le gouvernement central de la monarchie saoudienne. L'agriculture n'est pas à proprement parler le premier objectif de cette initiative, l'accent étant mis sur le tourisme et donc sur le vaste patrimoine historique et les qualités paysagères de la région. Néanmoins, l'agriculture et en particulier la phœniciculture restent la principale ressource des habitants. La caractérisation de l'agrobiodiversité locale des palmiers dattiers est essentielle pour le développement durable des oasis. À al‐'Ulā, la documentation des connaissances autochtones sur la variété locale barnī, prédominante, et la caractérisation de son identité génétique et de son mode de propagation représentent le levier nécessaire aux planificateurs de projets de développement agricole pour promouvoir la production locale.